The ecological footprint of swedish sugar consumption - Holmstrand, Karin (SLU/Dept. of Crop Production Ecology, 2019)
Climate change, loss of biodiversity and an ongoing population growth are challenging the global food production. Land is a scarce resource that is demanded for many purposes, reason why it is relevant to question how the arable land is used in the food production. Some commodities, including refined sugar, are not essential for the human diet, but are still consumed in higher quantities than are healthy for us. This report aims to investigate the ecological footprint of the sugar consumption in Sweden, focussing on land use. The research questions are: